L’institut océanographique de Paris - Christelle Inizan (In Situ)
Few years after the rebuilding of Sorbonne University, Henri-Paul Nénot, a parisian architect, was trusted to build three research and education institutes closeby. Two were ordered by the university: the geographic institute and the chemistry institute; and the third depended on a strictly private initiative. No one was really able to identify the genesis of this project of oceanographic institute initiated by Albert 1er de Monaco because of the lack of records; this will be the framework of our study. This article will attempt to analyze some constructive and decorative paths inherent to this typology of scientific establishments from the beginning of the twenty century. The human paleontology institute designed by the architect Pontremoli, is also attached to theses twenty century paths, and is a creation of the prince of Monaco.